PENGARUH PENERAPAN GREEN ACCOUNTING DAN KINERJA LINGKUNGAN TERHADAP SUSTAINABLE DEVEOPMENT DENGAN PROFITABILITAS SEBAGAI VARIABE MODERASI: Pada Perusahaan Sektor Industri Dasar dan Kimia yang Terdaftar di Bursa Efek Indonesia Tahun 2019 – 2021 - Muniroh Muniroh; Enggar Nursasi; Triani Triani (STIA MALANG, 2023)
This study aims to determine how much influence the application of environmental performance and green accountinghas on sustainable investment, with profitability as a moderation variabe. The study looked at 50 companies in thebasic and chemical industries listed on the Indonesia Stock Exchange (IDX) over a 3-year period, from 2019 to 2021.The number of observed data reached 150. To evaluate the effect of research variables, PLS SEM analysis techniquesare used. Analysis calculations show that green accounting has a significant influence on sustainable progress;environmental performance has no real effect on sustainable progress; Green accounting with profitability as amoderation variable has a noticeable influence on sustainable progress; And green accounting with profitability as amoderation variable has a real influence on sustainable progress. The calculation of this research analysis illustratesthat environmental performance with profitability